This language is not abandoned yet - Thuresson, Josefine (Konstfack, Institutionen för Konst (K), 2022)
This essay navigates around ideas of normality, assimilation, language politics and nationalism in relation to deafness and the history of the minority languages Swedish Sign Language and Meänkieli. It takes it starting point in how Audism has manifested itself within my family, a brief history of the education of the Deaf and Swedish Sign Language and continues by looking at how language oppression is used as a tool by the nation state, and ends with looking at art as proposals and methods of political resistance, expanding on the art form Visual Vernacular (VV), with the background of mine and Karin Keisu’s multi-channel film installation Back to Back (2022).